Optimalisasi Majelis Ta'lim Irsyadul Anam dalam Meningkatkan Pemahaman Agama di Desa Sukmajaya - Eda Laelasari; Ery Subaeri Ahmad; Moh. Romli; Syukron Makmun; Muhammad Yanto; Tina Sari; Noor Anisa Rahmawati; Evi Fusvitasari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to analyze the role of the Majelis Ta'lim Irsyadul Anam in enhancing religious understanding in Sukmajaya Village and the optimization strategies implemented. Majelis Ta'lim is one of the non-formal educational institutions that plays an important role in providing religious education to the community. The research method used is descriptive qualitative with data collection techniques through in- depth interviews, participatory observation, and documentation. The research informants include the committee members, the ustadz or ustadzah, and the congregation who actively participate in the activities. The research results show that the Majelis Ta'lim Irsyadul Anam plays a significant role in strengthening the congregation's understanding of religion through various study and lecture activities delivered using diverse methods, such as discussions, question and answer sessions, and the use of digital media. In addition, this assembly also provides personal guidance to congregants who need more in-depth instruction on worship and ethics. The optimization strategy is carried out by diversifying teaching methods and increasing the active participation of the congregation. In conclusion, the optimization of Majelis Ta'lim Irsyadul Anam in enhancing religious understanding in Sukmajaya Village has been successfully achieved through the implementation of interactive and innovative teaching methods, although there are still some obstacles that need to be addressed.